Sociological Aspects of Homicides in Lithuania - DOBRYNINAS, ALEKSANDRAS; KALPOKAS, VAIDAS; MICKEVIČ, ALINA (Kriminologijos studijos, 2014)
The paper presents the results of sociological researches carried out within the framework of the project “Homicides in Lithuania: Criminological Research” carried out in 2012–2013 and supported by the Research Council of Lithuania. The sociological part of the project was intended to analyze the social factors that influence the homicides, as well as public attitudes toward the murders. In order to achieve this goal, there were reviewed the existing criminological theoretical insights on this issue, as well as analyzed the empirical data on various social aspects of homicides. In the present publication, the authors discuss the social, economic, and geopolitical contexts of homicides in Lithuania, present the sociological portrait of a murder based on the analysis of 894 criminal cases, and scrutinize various aspects of public attitudes towards homicides, murders, their victims, and the role of governmental institutions in the homicides’ control and prevention in Lithuanian society. The statistical analysis of homicides and other negative social and economic indicators among European states reveals Lithuania to belong to the so-called “post-Soviet cluster” that may indirectly point at the historical socio-political roots of homicides in the country. It could also explain the dramatically high rate of homicides in Lithuania and other Baltic countries as compared with the European Union states. The study of criminal cases in Lithuania demonstrates peculiarities in murderers’ age and gender: in principle, only younger people commit group murders, among their victims there often are other men; women, differently than men, both in case of being a murderer or a victim, usually have close or family relations with the other participants of the crime incident. The results of a national survey show that respondents are able to differentiate murder’s cases and the appropriate sanctions. Most of respondents believe that the reduction of the number of homicides in society is linked with a severe and effective execution of criminal penalties, but at the same time they also are in favor of the homicides’ control and prevention program.
Keywords: homicides; macro-social context; sociological portrait of murderer; public attitudes towards homicides